2018
DOI: 10.1016/j.jacc.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events Associated With SGLT-2 Inhibitors Versus Other Glucose-Lowering Drugs

Abstract: In this large, international study of patients with T2D from the Asia Pacific, the Middle East, and North America, initiation of SGLT-2i was associated with a lower risk of CV events across a broad range of outcomes and patient characteristics. (Comparative Effectiveness of Cardiovascular Outcomes in New Users of SGLT-2 Inhibitors [CVD-REAL]; NCT02993614).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
380
1
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 414 publications
(438 citation statements)
references
References 24 publications
35
380
1
22
Order By: Relevance
“…With consistent evidence of the beneficial effects of SGLT‐2is on CV risk and their strengthened position in guidelines, it is of high importance to understand the actual patient profiles in these CVOTs and, thereby, how representative of a general T2D population the included patient populations actually are . From the present analysis, it is clear that the main inclusion criteria, determining the baseline CV risk in the respective CVOT, are closely correlated to how representative of a general T2D population the trials are in comparison with each other.…”
Section: Discussionmentioning
confidence: 75%
“…With consistent evidence of the beneficial effects of SGLT‐2is on CV risk and their strengthened position in guidelines, it is of high importance to understand the actual patient profiles in these CVOTs and, thereby, how representative of a general T2D population the included patient populations actually are . From the present analysis, it is clear that the main inclusion criteria, determining the baseline CV risk in the respective CVOT, are closely correlated to how representative of a general T2D population the trials are in comparison with each other.…”
Section: Discussionmentioning
confidence: 75%
“…Unlike the EMPA‐REG OUTCOME trial and the CANVAS study, which compared SGLT2 inhibitors to placebo, the current study used active comparators which is more relevant to guidance concerning prescribing decisions in routine clinical practice . Observational studies, such as the CVD‐REAL study, have compared SGLT2 inhibitors to other glucose‐lowering agents, with conflicting findings . In the first follow‐up analysis of the CVD‐REAL study, the authors did not find a significant difference between use of dapagliflozin and use of DPP‐4 inhibitors in risk of MI and stroke, but subsequent analyses reported a reduction in risk .…”
Section: Discussionmentioning
confidence: 92%
“…Several observational studies have recently evaluated the cardiovascular safety of SGLT2 inhibitors among patients with type 2 diabetes . One population‐based study, which used data from the Health Improvement Network database, found that, compared to use of other glucose‐lowering agents, the use of empagliflozin was associated with lower risk of all‐cause mortality, irrespective of baseline CVD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Dapagliflozin, approved for treatment of T2DM, may also be effective in patients with T1DM. [14][15][16][17] Dapagliflozin, approved for treatment of T2DM, may also be effective in patients with T1DM.…”
Section: Introductionmentioning
confidence: 99%